Highly Selective Catalytic Spectrophotometric Determination of Copper in Water Samples - BAGHERI*, H.; TABATABAEE, M.; KERDEGARI, A.A.; SHAHVAZIAN†, M.; SHISHEHBORE, M.R. (Asian Journal of Chemistry, 2009)
A simple, rapid and sensitive method has been developed for determinationof trace amounts of copper(II) (1-160 ng mL-1) based on it'scatalytic effect on the oxidation of thionine by hydrogen peroxide in analkaline media and in the presence of o-phenanthroline as an activator.The reaction is monitored spectrophotometrically by measuring thedecrease in absorbance of thionine at 600 nm by the fixed time method.The detection limit is 0.7 ng mL-1 and relative standard deviation forten replicate determinations of 2, 20, 50 and 100 ng mL-1 copper were1.71, 1.2, 0.98 and 0.75 %, respectively. The proposed method is sensitive,accurate and tolerant to many foreign substances and all the reagentsused are stable under the conditions. Moreover, the method is easy toperform for the determination of copper in real samples.